Dampak Antusiasme Penggemar Konser Online BTS terhadap Euforia Korean Wave di Media Sosial Fanbase BTS di Indonesia - Martanu, Gavrila Claudia; Candraningrum, Diah Ayu (Prologia, 2025)
Korean Wave or Hallyu phenomenon has become a global cultural trend which has attracted the attention of the global community, especially through music groups such as BTS. This study seeks to examine the impact of the enthusiasm regarding BTS Online concert fans on the euphoria of the Korean Wave on social media. Using a questionnaires were distributed to collect data using quantitative techniques means of obtaining data. In this research, Parasocial Interaction Theory is used to explain the strong relationship between Bangtan Seonyeondan (BTS) fans and the group, even though only through digital platforms such as social media and Online concerts. The population of this study consisted of Instagram followers accounts of Bangtan Seonyeondan (BTS) fans in Indonesia with a sample of 100 individuals determined through calculations using the Slovin's formula. The results of the study show that there is an influence of the enthusiasm of BTS Online Concert fans on the euphoria of the Korean Wave on BTS Fanbase social media in Indonesia. Through the findings of statistical tests carried out, the R Square value is 0.680, this shows indicating an effect of the independent variable. (fan enthusiasm) on the outcome variable (Korean Wave) of 68.0%. FFenomena Korean Wave atau Hallyu telah menjadi salah satu tren budaya global yang menarik perhatian masyarakat internasional, terutama melalui grup musik seperti BTS. Penelitian ini bertujuan untuk menganalisis pengaruh antusiasme penggemar konser Online BTS terhadap euforia Korean Wave di media sosial, dengan pendekatan kuantitatif, data diperoleh melalui penyebaran kuesioner sebagai sarana untuk mendapatkan data. Dalam penelitian ini digunakan Teori Interaksi Parasosial untuk menjelaskan adanya hubungan yang kuat di antara penggemar Bangtan Seonyeondan (BTS) dengan grup tersebut, meskipun hanya melalui platform digital seperti media sosial dan konser Online. Populasi dalam penelitian ini terdiri dari pengikut akun Instagram penggemar Bangtan Seonyeondan (BTS) di Indonesia dengan sampel berjumlah 100 orang yang didapat melalui perhitungan dengan menggunakan rumus Slovin. Hasil penelitian menunjukkan bahwa terdapat pengaruh antusiasme penggemar konser Online BTS terhadap euforia Korean Wave di media sosial Fanbase BTS di Indonesia. Melalui hasil uji statistik yang dilakukan, nilai R Square merujuk pada 0,680, ini mengindikasikan bahwa terdapat pengaruh dari variabel independen (antusiasme penggemar) pada variabel dependen (Korean Wave) senilai 68,0 %.